Health Benefits of Tea Polyphenols and Mechanisms via Regulating Gut Microbiota - Xu, Xinyue (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Tea has been a beloved beverage for centuries, enjoyed by people all over the world. Tea polyphenols, natural bioactive compounds abundant in tea, have gained increasing attention for their potential health-promoting properties. This study provides a comprehensive overview of the multifaceted interactions between tea polyphenols and gut microbiota, shedding light on their roles in health and disease prevention. The opening section provides an in-depth examination of the definition and categorization of tea polyphenols, and their prevalence in various types of tea. Subsequently, the following section conducts an extensive analysis of the crucial role played by gut microbiota and the ways in which tea polyphenols modulate their composition, including their potential as prebiotic agents. In addition, this paper discusses the diverse health-promoting aspects of tea polyphenols, such as their antioxidative properties, anti-inflammatory effects, and their potential impact on conditions like inflammatory bowel diseases (IBD) and colorectal cancer, furthermore, explores their role in addressing functional disorders like depression and combating fatigue. This paper highlights the intricate interplay between tea polyphenols and gut microbiota and underscores the potential significance of these interactions in promoting health, advancing the understanding of the role of tea polyphenols in wellness and disease prevention.